The role of the commensal microbiota in the regulation of tolerance to dietary allergens. Issue 3 (June 2015) - Berni Canani, Roberto; Gilbert, Jack A.; Nagler, Cathryn R.
Abstract : Purpose of review: We review the evidence that environmental stimuli that perturb naturally selected host–microbe interactions are driving the increasing prevalence of food allergy and examine the mechanisms by which commensal bacteria regulate tolerance to dietary allergens. Recent findings: Antibiotic use and the consumption of a high-fat/low-fiber diet have a major and rapid impact on gut bacterial populations, with long-term consequences for both overall microbial community structure and the regulation of host immunity. Recent work emphasizes the role of mucosa-associated commensal bacteria in eliciting a barrier-protective response critical to preventing allergic sensitization to food. Murine model studies are informing the development of novel live biotherapeutic approaches as an adjunctive therapy to enhance antigen-specific oral desensitization and to promote lasting tolerance in patients with food allergy. Summary: Strategies based on modulating the composition and/or functionality of the gut microbiome hold promise for the treatment of food allergy.